2019
DOI: 10.1088/1755-1315/305/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor of secretory immunoglobulin A and salivary lysozyme level in children aged under 3 years to severe early childhood caries

Abstract: Severe Early Childhood Caries (SECC) is a significant dental health problem in various countries. The caries pathology process is affected by saliva status. An important antimicrobial component in saliva is sIgA preventing the attachment of bacteria to enamel and lysozyme capability to act as an antibacterial by hydrolyzing bacterial polysaccharide walls. The aim of the study is to compare the sIgAlevel and salivary lysozyme between children with caries free and suffering from SECC, aged under 3 years. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
3
2
Order By: Relevance
“…The results of Primasari et al [ 41 ] and Al-ani et al [ 20 ] found that there was no difference in salivary s-IgA levels between caries-free people and caries patients, which was contradictory with the results of the present study. The results obtained by the above studies may be due to the small sample size and different criteria for judging dental caries.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of Primasari et al [ 41 ] and Al-ani et al [ 20 ] found that there was no difference in salivary s-IgA levels between caries-free people and caries patients, which was contradictory with the results of the present study. The results obtained by the above studies may be due to the small sample size and different criteria for judging dental caries.…”
Section: Discussioncontrasting
confidence: 99%
“…However, some studies have suggested that microorganisms can protect themselves from host immune attack by forming biofilms and reducing the expression of antigens [65, 66], which will cause higher levels of s-IgA in the saliva of healthy people than patients with caries. Dental caries was caused by the imbalance between enamel The results of Primasari's et al [41] and Al-ani's et al [20] found that there was no difference in salivary s-IgA levels between caries-free people and caries patients, which was contradictory with the results of this study. The results obtained by the above studies may be due to the small sample size and different criteria for judging dental caries.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Lysozyme, as a hydrolytic enzyme, breaks down cellular membranes gram-positive and gram-negative bacteria, fungi and viruses. It is one of the key antimicrobial factors of the oral fl uid [10]. Therefore, determination of the activity of this enzyme is informative concerning its eff ect on the state of local non-specifi c immunity, which is the fi rst-line protection against microbe-associated pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Dental caries have a relationship with several factors, such as tooth condition, carbohydrate fermentation, and acid production from bacteria in the oral cavity. 3 It is caused by demineralization of the tooth, which is triggered by the production of organic acids by bacteria in dental plaque resulting from carbohydrate metabolism. 4,5 One strategy to prevent caries is to inhibit the demineralization process in the tooth through the use of minerals containing bioactive glass nano-silica, such as bagasse ash.…”
Section: Introductionmentioning
confidence: 99%